Taxonomic review of Polynema (Hymenoptera: Mymaridae) in Australia and New Zealand, with descriptions of eight new species - Triapitsyn, Serguei V. (Zootaxa, 2021)
Two Australian species of Polynema Haliday (Hymenoptera: Mymaridae), P. (Polynema) draperi Girault and P. (Polynema) editha Girault, are redescribed, as is the Australasian and Oriental P. (Dorypolynema) mendeli Girault; the previously unknown female of P. draperi and male of P. editha are also described. One new species group, the draperi group, is newly defined in P. (Polynema), in which eight new species are described: P. (Polynema) aristokratka sp. n. (New Zealand), P. (Polynema) baronessa sp. n. (New Zealand), P. (Polynema) grafinya sp. n. (New Zealand), P. (Polynema) imperatrix sp. n. (Australia), P. (Polynema) koroleva sp. n. (New Zealand), P. (Polynema) markiza sp. n. (New Zealand), P. (Polynema) princessa sp. n. (Australia), and P. (Polynema) rangatira sp. n. (New Zealand). Keys to the two treated subgenera of Polynema, both sexes of the world species of P. (Dorypolynema Hayat & Anis), and to females of the 10 described P. (Polynema) species in Australia and New Zealand are given. Taxonomic notes are provided for the Afrotropical species Polynema (Dorypolynema) mboroense (Risbec), comb. n. from Acmopolynema Ogloblin, whose previously unknown female is described, and for the Australian species Palaeoneura frater (Girault), comb. n. from Polynema.